Cardiorespiratory fitness and all‐cause mortality in adults diagnosed with cancer systematic review and meta‐analysis. (14th May 2021) - Ezzatvar, Yasmin; Ramírez‐Vélez, Robinson; Sáez de Asteasu, Mikel L.; Martínez‐Velilla, Nicolás; Zambom‐Ferraresi, Fabricio; Lobelo, Felipe; Izquierdo, Mikel; García‐Hermoso, Antonio
Abstract : Introduction: The inverse association between cardiorespiratory fitness and all‐cause mortality in apparently healthy populations has been previously reported; however, the existence of this association among adults diagnosed with cancer is unclear. Aim: To determine the association between cardiorespiratory fitness and all‐cause mortality in adults diagnosed with cancer. Methods: Medline, Embase, and SPORTDiscus databases were searched. Eligible prospective cohort studies that examined the association of cardiorespiratory fitness with all‐cause mortality in adults diagnosed with cancer were included. Hazard ratios (HRs) with associated 95% confidence intervals (CIs) were extracted from studies for all‐cause mortality and pooled HRs were calculated using the random‐effects inverse‐variance model with the Hartung‐Knapp‐Sidik‐Jonkman adjustment. Results: Data from 13 studies with 6, 486 adults were included. Compared with lower levels of cardiorespiratory fitness, high levels were associated with a reduced risk of all‐cause mortality among adults diagnosed with any cancer (HR = 0.52; 95% CI, 0.35–0.77), lung cancer (HR = 0.62; 95% CI, 0.46–0.83), and among those with cardiorespiratory fitness measurement via indirect calorimetry (HR = 0.47; 95% CI, 0.27–0.80). Pooled HRs for the reduction in all‐cause mortality risk per 1‐MET increase were also statistically significant (HR = 0.82; 95% CI, 0.69–0.99). Neither age at baseline nor the length of follow‐up had a significant influence on the HR estimates for all‐cause mortality risk. Conclusion: Cardiorespiratory fitness may confer an independent protective benefit against all‐cause mortality in adults diagnosed with cancer. The use of cardiorespiratory fitness as a prognostic parameter might help determine risk for future adverse clinical events and optimize therapeutic management strategies to reduce long‐term treatment‐related effects in adults diagnosed with cancer.